Doing criminological research - Davies, Pamela, 1962-; Francis, Peter, 1968-; Jupp, Victor. (SAGE, 2011)
This is a highly practical examination of the key issues regarding the practices and principles of research methods contextualised within studies of crime and criminal justice.